Influence of the ginning machine saws speed in the quality of cotton fiber - Beyer Arteaga, Alfredo Alberto (2020)
Cotton is an important industrial crop in the textile sector, it is the most important natural fiber produced in the world. The quality of cotton fiber is mainly reflected in length, fineness and resistance. The cotton fiber arrives attached to the seeds from the field and goes through the ginning process. The objective of the present study was to find a relationship between the RPM speeds at which the saw gin works used for cotton ginning, and the fiber length, fineness and resistance. Data were obtained from the average of ten samples, ten samples of between 18 and 20 grams of cotton fiber were used as an experimental unit. The response variables were the length of 2.5% of the fiber, 50, 60 and 70%, as well as the fineness and strength of the fiber. The experimental design was a CRD with nine repetitions and three treatments that were 700, 650 and 580 RPM. A significant difference between treatments was found for the variable Length of 2.5% of the fiber, the most used commercially, the shorter length being that of the 700 RPM treatment, which indicates that the faster the saws work, there is an increase of the mistreatment of the fiber, whose effect is the shortening of the same. However, there was no statistical difference in the variables L50%, L60% and L70%. A causal relationship could not be established for the fineness variable, as indicated in the literature, and finally no significant difference was found in the resistance variable with respect to the speed at which the saws work. In conclusion, the speed at which the saws of the cotton ginning machine work influences the quality of the fiber, mainly in the length of the same; It is recommended to use 580 or 650 RPM.